PENERAPAN MANAJEMEN KURIKULUM BERBASIS CINTA DI ERA DIGITAL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN INOVATIF DI MI - Sigit Candra Nuraziz; Annisa Lutfiana; Istifa Ayuning Lazuardy; Muhammad Fahmi Cholqi; Hizbul Muflihin (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of love-based curriculum management in the digital era to enhance the quality of innovative learning at MI Muhammadiyah Pasirmuncang. The love-based curriculum emphasizes values of compassion, empathy, and social care as the foundation of learning, integrating cognitive, affective, and spiritual dimensions of students’ development. This research employed a qualitative descriptive approach, with data collected through interviews, observations, and documentation studies involving teachers and educational staff. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings reveal that love-based curriculum management is implemented through flexible and adaptive strategies, student-centered learning, integration of digital technology, and active collaboration among school principals, teachers, educational staff, and parents. The values of love are integrated into learning processes through role modeling, habituation of noble values, authentic learning experiences, and ethical and empathetic use of digital media. The implementation of love-based curriculum management effectively fosters innovative, humanistic, and collaborative learning that is responsive to the challenges of education in the digital era.